Distribusi Spasial–Temporal Produksi Sampah di Pangkalan Pendaratan Ikan (PPI) Cituis: Distribusi temporal produksi sampah di Pangkalan Pendaratan Ikan(PPI) Cituis - Andi Admiral Farouk Sabzevar; Hefni Effendi; Sigid Hariyadi; Gatot Yulianto (Habitus Aquatica, 2026)
This study aims to analyze garbage waste data by day in a week at the Cituis Fish Landing Base (PPI Cituis), identify the causes of waste issues, and provide recommendations for waste management and handling. The research was conducted over two weeks of observation. Data were collected through waste characterization, total and average garbage waste volume measurements, the number of waste containers, and waste type composition from several source points. The results show that waste volume tends to increase at the end of the month, on weekends, and during holidays, following higher visitor numbers and fishing activities. Inorganic waste, especially plastic was the most dominant type across all port zones. The 3 kg container representing the harbor area had the highest percentage of waste bins compared with the 4 kg and 10 kg containers. Proper waste management is necessary to minimize pollution impacts at PPI Cituis and the surrounding environment. Recommended actions include improving waste facilities, strengthening governance and regulations, and enhancing community awareness and participation.